(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
This article tells a story about cannabis that illuminates two dimensions of its development that are often overlooked for a truly liberating development plan post legalization for the majority of people in South Africa. Firstly, by its nature cannabis is political and has a black revolutionary history that is not being adequately acknowledged in the contemporary literature, even though it is deeply embedded in how the plant is understood in the geographic diaspora of the Global South. Secondly, any serious social scientific analysis of contemporary cannabis development must think through how the ways of knowing and work, produced during prohibition, will become a part of the plant’s future. Innovative and alternative models of practical development are agencies of the marginalized majority that should become a standard part of the geographies of all work economies. The article shows that because prohibition narratives, particularly regarding recreational usage, continue to hold substantial power over how societies understand cannabis, delinking from these inscriptions onto the plant is essential for its future development. The article argues further that the current trend towards the medicalisation of cannabis is not fully transformative for Global South development because it reforms rather than stamp out gatekeeping models. Lastly, it exposes the realities of gaining access into the industry for black people, the poor working class and women. It argues that ownership, just employment and leadership of cannabis industries in South Africa must also be performed by ordinary people for a truly sustainable contemporary development.